The Relationship between Work Motivations, Job Autonomy, Emotional Burnout and Job Satisfaction among Women Working in Tourism in Jordan - ALLAN, Mamoon (Journal of Environmental Management and Tourism, 2019)
To date, the nature and scope of work for Arabic women in the tourism and hospitality has received scant attention in the research literature. Therefore, this study aims to examine the relationship between work motivations, emotional Burnout, job autonomy, and job satisfaction for a sample of females working in various sectors of tourism in Jordan. Quantitative methodology was employed, consisting of a self-administered questionnaire. Of 300 female employees, 212 have been selected for further analysis in this study. The main findings of this study indicate that there is a strong relationship between job autonomy and the satisfaction dimensions. The study further shows that intrinsic motivation was a good predictor for supervision, whilst extrinsic motivation correlates positively with co-workers. Also, this study has revealed that amotivation state is a weak predictor for job satisfaction dimensions. Implications for tourism practitioners are presented, along with different areas of future research.